The Influence of Attitude, Subjective Norm, Perceived Behavioral Control, Purchase Intention, and Nutritional Awareness on the Purchase Behavior of Nutritious Food and Beverage Products among Adolescents in Indonesia - Rezky Aulia Yusuf; Nurul Hikmah Baharuddin; Aqila Salzabila Marzuki; Nurul Awalia (Global Health Practice Journal, 2025)
Adolescence is a critical developmental stage that requires adequate nutritional intake to support physical, mental, and social growth. However, many adolescents adopt unhealthy eating behaviors influenced by trends, peer pressure, and limited nutritional awareness. This study analyzed the influence of attitude, subjective norms, perceived behavioral control, purchase intention, and nutritional awareness on the purchase behavior of nutritious food and beverages among adolescents in Makassar. Using a cross-sectional research design, data were collected from 119 students at SMA 10 Makassar through a structured questionnaire. Logistic regression analysis revealed that attitude (COR = 10.41, p = 0.001) and purchase intention (COR = 12.22, p = 0.001) significantly affected nutritious food purchasing behavior. Meanwhile, subjective norms, perceived behavioral control, and nutritional awareness did not show significant effects. These findings highlight the importance of developing youth-oriented nutrition programs that strengthen positive attitudes and purchasing motivation toward nutritious food products.